2015
DOI: 10.1007/s13593-015-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Luxembourgish farmers’ lack of information about grain legume cultivation

Abstract: Grain legume production in Europe has decreased in recent years, while legume demand has rapidly increased due to growth of meat production. Therefore, Europe imports grain legumes, principally soybeans, to meet feed protein requirements. Various investigations have identified problems and benefits of local grain legume cultivation. Nevertheless, grain legume cultivation has still not increased in the last years. Studies investigating why farmers do not cultivate grain legumes are missing. Here, we surveyed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 13 publications
1
34
1
Order By: Relevance
“…Other approaches and theoretical frameworks, in agronomy or economics, could have been used to analyze the increase in areas of major crops and the decline of minor crops, and to model these trends. Several studies, based on such disciplinary approaches, are quoted in our paper (for example, in agronomy, Schott et al 2010;Ponisio et al 2015;Zimmer et al 2016;in economics, Fares 2006;Filippi et al 2008;Louhichi et al 2017). However, the complex and systemic characters of specialization led us to overpass these disciplinary approaches, to adopt a holistic perspective of the involved socio-technical factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other approaches and theoretical frameworks, in agronomy or economics, could have been used to analyze the increase in areas of major crops and the decline of minor crops, and to model these trends. Several studies, based on such disciplinary approaches, are quoted in our paper (for example, in agronomy, Schott et al 2010;Ponisio et al 2015;Zimmer et al 2016;in economics, Fares 2006;Filippi et al 2008;Louhichi et al 2017). However, the complex and systemic characters of specialization led us to overpass these disciplinary approaches, to adopt a holistic perspective of the involved socio-technical factors.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted from yield increase and input use reduction on the subsequent wheat (compared to wheat following wheat). The lack of similar references for all minor crops, in the different agro-climatic areas, is an impediment to diversification, as confirmed by Zimmer et al (2016) in Luxembourg.…”
Section: Farmingmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite such well-known benefits, various studies have shown the adoption of diversification practices to be limited by barriers at all levels of food systems. These barriers are related to "regime rules" [19] historically established to support largescale specialisation and short-term maximisation of profits with chemical inputs [16,31,[35][36][37][38]. We posit that crop diversification is specifically relevant as it can be promoted both outside and within the regime [2,30].…”
Section: Contrasting Food System Innovation Settings For Crop Diversimentioning
confidence: 99%
“…Expanding production of grain legumes also faces difficulties due to technological lock-in of production systems, resulting from co-evolution of interrelated organizations, technologies, knowledge, values, and environments, which discourages actors from adopting alternative technologies, even if they are more beneficial (Magrini et al 2016). For example, a recent study of farmers in Luxembourg identified that a major obstacle to growing grain legumes is a lack of knowledge about them and of extension services for them (Zimmer et al 2016).…”
Section: Introductionmentioning
confidence: 99%